2023
DOI: 10.1021/acs.jpcc.3c02934
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Adsorbate–Solvent Interactions: Are Dispersion Corrections Necessary?

Abstract: Incorporating solvent−adsorbate interactions is paramount in models of aqueous (electro)catalytic reactions. Although a number of techniques exist, they are either highly demanding in computational terms or inaccurate. Microsolvation offers a trade-off between accuracy and computational expenses. Here, we dissect a method to swiftly outline the first solvation shell of species adsorbed on transition-metal surfaces and assess their corresponding solvation energy. Interestingly, dispersion corrections are genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The free energies of reaction were evaluated using the formula: Δ G ≈ Δ E DFT + ΔZPE – TΔ S + Δ E solv , where Δ E DFT is the DFT-calculated reaction energy, ΔZPE is the zero-point energy change, TΔ S is the entropy change at 298.15 K, and Δ E solv is a solvation correction for adsorbates calculated by means of an iterative microsolvation method , (see further details and specific values in Section S3). Δ S of free molecules were obtained from thermodynamic tables, while for adsorbates, Δ S only includes vibrational entropies.…”
Section: Methodsmentioning
confidence: 99%
“…The free energies of reaction were evaluated using the formula: Δ G ≈ Δ E DFT + ΔZPE – TΔ S + Δ E solv , where Δ E DFT is the DFT-calculated reaction energy, ΔZPE is the zero-point energy change, TΔ S is the entropy change at 298.15 K, and Δ E solv is a solvation correction for adsorbates calculated by means of an iterative microsolvation method , (see further details and specific values in Section S3). Δ S of free molecules were obtained from thermodynamic tables, while for adsorbates, Δ S only includes vibrational entropies.…”
Section: Methodsmentioning
confidence: 99%
“…[70] On the other hand, dispersion effects have a negligible impact on the relative stability, adsorption sites, and adsorption geometries of water adstructures. [71,72] In addition, Romeo et al [73] have additionally shown that dispersion corrections are generally not significant when water-adsorbate interactions prevail. Therefore, to assess the need of dispersion corrections for our given system, we have incorporated additional calculations that include D3 dispersion corrections with zero damping.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…On the other hand, dispersion effects have a negligible impact on the relative stability, adsorption sites, and adsorption geometries of water adstructures [71,72] . In addition, Romeo et al [73] . have additionally shown that dispersion corrections are generally not significant when water‐adsorbate interactions prevail.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…The former describes the electrolyte by the direct inclusion of solvent molecules in the calculation, although there are several variants within the umbrella term of explicit solvation. For example, there are reports of systems modelled with a discrete number of water molecules, 5–7 an ice-like water layer, 8,9 or with the simulation cell completely filled with water molecules. 10 Regardless of the method adopted, the description of the electrolyte via explicit models is further complicated by the fact that the solid–liquid interface is dynamic; in other words, a vast number of configurations of the interface can exist.…”
Section: Introductionmentioning
confidence: 99%